From Offsetting to Emulation: A Neoclassical Realist Analysis of Russia’s Internal Balancing Strategies - Dall'Agnol, Augusto (2022)
In 2008, Russia began to implement its largest military reform since the creation of the Red Army in 1918. Previous attempts at reforms in 1992, 1997, and 2003 did not result in fundamental transformations to the country’s military. Why was the 2008 military reform successful while others were not? This article uses the comparative-historical method to identify the causal mechanisms between Russia’s level of external threat, state capacity, and internal balancing strategies adopted since 1991. It advances Neoclassical Realism’s systemic and unit-level variables by building on the long-established contributions from Strategic Studies and Historical Sociology instead of relying on other International Relations theories. It concludes that the success of Russia’s military reforms in the post-Cold War period depended on the simultaneous existence of three conditions: the possibility of disrupting strategic stability, its ability to extract and mobilize societal resources, and the presence of some event of proven ineffectiveness. Under scenarios in which only one or two of these conditions were present, Russia carried out only partial military reforms. The article sheds light on three often-neglected drivers of Russia’s military reform by Western analysts: its enduring emphasis on interstate competition, strategic stability, and mid-to-high intensity conventional warfare.